Exploring the Role of Open Family Communication in a Child's Self-Adjustment with Stepmother - Fitriana, Luthfia Nur; Ramadhana, Maulana Rezi (JURNAL LENSA MUTIARA KOMUNIKASI, 2024)
This qualitative research investigates the significance of open family communication in children's adaptation to the presence of a stepmother. Through in-depth interviews with five child informants, we explore crucial factors such as the introduction process, the journey from discomfort to closeness, and the influence of parental communication and openness on children's ability to adapt and establish relationships with their stepmothers. The study also delves into the evolving dynamics of emotional expression, acceptance, and the impact of early experiences on the relationships between children and their stepmothers. Furthermore, we examine the unique roles of stepmothers, communication challenges, and the effects of the COVID-19 lockdown on the depth of conversations. The findings contribute valuable insights to understanding the complexities of children's adjustment within blended families, emphasizing the pivotal role of open family communication in nurturing healthy relationships.